2001
DOI: 10.1023/a:1010621901102
|View full text |Cite
|
Sign up to set email alerts
|

CK-19 Expression by RT-PCR in the Peripheral Blood of Breast Cancer Patients Correlates with Response to Chemotherapy

Abstract: We conclude that RT-PCR negativity for CK-19 expression at 3 months after the beginning of chemotherapy correlates with tumor response and, as treatment progresses, there is a significant trend for the occurrence of more negative RT-PCR results. Further studies are needed to confirm if this technique can be useful to assess response to chemotherapy in patients without measurable disease and if negativation of CK-19 expression while on chemotherapy is of prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…We can, however, assess its rate of positivity. In this study it reached 31% (95% CI: 30-33%) which is similar to that of RT-PCR in the peripheral blood of BC patients according to several authors [24,25] and with a recent metaanalysis conducted by one of the authors [26]. It is possible, therefore, that less invasive and easier methodologies such as the detection of circulating epithelial cells in the peripheral blood of BC patients may, in the future, substitute BM IC.…”
Section: Discussionsupporting
confidence: 83%
“…We can, however, assess its rate of positivity. In this study it reached 31% (95% CI: 30-33%) which is similar to that of RT-PCR in the peripheral blood of BC patients according to several authors [24,25] and with a recent metaanalysis conducted by one of the authors [26]. It is possible, therefore, that less invasive and easier methodologies such as the detection of circulating epithelial cells in the peripheral blood of BC patients may, in the future, substitute BM IC.…”
Section: Discussionsupporting
confidence: 83%
“…The accuracy of CTC load comparison by Q-RT-PCR would depend on the degree of constancy of CK19 or other chosen marker expression over time. Indirect evidence from a study following patients during the course of chemotherapy suggests that stability of CK19 was sufficient to detect the correlation with treatment outcome [7]. Highly correlative gene expression profiles of core biopsies and resected tumors temporally spaced within days and weeks also suggest relative constancy of the marker genes within short but clinically important periods of time [21].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter prospective study compared different quantities of CTCs in relation to outcome and showed that patients with more than five CTCs per 7.5 ml of blood had a shorter progression-free and overall survival (2.7 months vs. 7.0 months and 10.1 months vs. >18 months) [6]. Noticeably decreased levels of CTCs are seen in response to chemotherapy suggesting a role for measurement of CTCs in treatment monitoring [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Such an example is the utilisation of tyrosinase, an enzyme present only in melanocytes, for the detection of MRD in melanoma patients (Li et al, 2000). In breast cancer patients, molecules such as CK, expressed in epithelial cells but not expressed in lymphocytes, were investigated (Kruger et al, 1996;Manhani et al, 2001;Ismail et al, 2003). Using PCR to detect nonspecific epithelial markers may yield a robust and simple assay for the detection of MRD in patients with epithelial-derived tumours.…”
Section: Discussionmentioning
confidence: 99%